Evaluation and Recognition of Indian English - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 6 No 2 (2021): Journal of Advanced Research in English & Education, 2021)
Indian English (IE) is a variety of the English language spoken in India and among the Indian diaspora elsewhere in the world. English is used by the Indian government for communication as a supplement to Hindi, the countryâ€™s â€œofficial language of the Unionâ€ enshrined in the Constitution. English is an official language of 7 states and 5 Union Territories and also an additional official language of the Judiciary of India, unless a state Governor or legislator mandates the use of regional language, or the President has given approval for the use of regional languages in courts. How to cite this article: Priydarshi AK. Evaluation and Recognition of Indian English. J Adv Res Eng & Edu 2021; 6(2): 5-9. DOI: https://doi.org/10.24321/2456.4370.202102